Geographical and discursive variation of discourse-connective que in Spanish - Pérez Fernández, Sofía; Gras, Pedro; Brisard, Frank (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This study presents a corpus-based analysis of discourse-connective que (DCQ) in five varieties of Spanish and across four different discursive genres. On the one hand, we show that DCQ is not only a spoken phenomenon but at the same time mainly restricted to colloquial language use. On the other hand, the results show that DCQ is more entrenched in the Peninsular variety than in the Latin-American varieties (Mexico shows the lowest overall frequency). Moreover, we also analyze geographical variation regarding the position in which DCQ is located in the turn of the speaker (heading the turn or not), distinguishing between three different profiles associated with specific regions: i) Spain, where DCQ is mostly found in initial position, ii) Argentina, the Caribbean and Mexico, where DCQ is primarily used in non-initial position, and iii) Chile, where DCQ is almost equally distributed between initial and non-initial positions. Finally, we also attested differences across language varieties regarding the type of turn in which DCQ occurs (initiation, preferred response and dispreferred response) and the internal structure of the turn (utterance in a complex turn vs turn extension, for multiturn units).